The compounding effect of mandatory GHG emissions disclosure and voluntary ESG disclosure on firm value in Korea - Kim, Sangil; Kim, Kimin (Journal of Asian Business and Economic Studies, 2024)
Purpose: This study attempts to examine the effect of greenhouse gas (GHG) emissions disclosure and its compounding effect with environmental, social, and governance (ESG) disclosure on firm value in Korea. This study focuses on the unique institutional setting in Korea that implements mandatory GHG emissions disclosure and voluntary ESG disclosure. Design/methodology/approach: Using a dataset comprising 25,968 firm-year observations from publicly listed Korean firms from 2000 to 2021, we applied an ordinary least squares (OLS) regression model to test hypotheses. Findings: The results show that, in a voluntary disclosure regime, ESG disclosure has a positive impact, whereas in a mandatory disclosure regime, GHG emissions disclosure has a negative impact on firm value. The results also indicate that when a firm discloses both its GHG emissions and ESG performance information, the voluntary disclosure of ESG information synergistically mitigates the adverse effects of mandatory disclosure of GHG emissions information. This synergy contributes significantly to enhancing the firm’s overall value. The findings indicate that a firm can enhance its value by proactively disclosing ESG information, especially when it is compulsorily required to report GHG emissions data. Originality/value: This study investigated the effect of corporate non-financial disclosure on firm value by shedding light on the differential attributes between voluntary and mandatory disclosures and between quantitative and qualitative information.
Keywords: ESG disclosure; GHG emissions disclosure; Korea; Mandatory disclosure; Voluntary disclosure